2022
DOI: 10.1001/jamanetworkopen.2022.43163
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Uptake Appropriateness of Computed Tomography for Lung Cancer Screening According to Patients Meeting Eligibility Criteria of the US Preventive Services Task Force

Abstract: ImportanceCurrently, computed tomography (CT) is used for lung cancer screening (LCS) among populations with various levels of compliance to the eligibility criteria from the US Preventive Services Task Force (USPSTF) recommendations and may represent suboptimal allocation of health care resources.ObjectiveTo evaluate the appropriateness of CT LCS according to the USPSTF eligibility criteria.Design, Setting, and ParticipantsThis cross-sectional study used the 2019 Behavioral Risk Factor Surveillance System (BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…According to limited information about comorbid conditions presented in the present study by Liu et al, 5 individuals who did not undergo screening despite meeting USPSTF criteria appeared to have fewer comorbid conditions than those who were screened by self-report, although substantial numbers in both groups reported a history of chronic obstructive pulmonary disease (>30%), depression (>25%), diabetes (>20%), and myocardial infarction (>15%). Prior analyses of the 2017 to 2019 BRFSS data observed that, among participants who reported undergoing lung cancer screening, 28% had 3 or more chronic comorbid conditions.…”
Section: Opencontrasting
confidence: 61%
See 4 more Smart Citations
“…According to limited information about comorbid conditions presented in the present study by Liu et al, 5 individuals who did not undergo screening despite meeting USPSTF criteria appeared to have fewer comorbid conditions than those who were screened by self-report, although substantial numbers in both groups reported a history of chronic obstructive pulmonary disease (>30%), depression (>25%), diabetes (>20%), and myocardial infarction (>15%). Prior analyses of the 2017 to 2019 BRFSS data observed that, among participants who reported undergoing lung cancer screening, 28% had 3 or more chronic comorbid conditions.…”
Section: Opencontrasting
confidence: 61%
“…Indeed, a modeling study from the Cancer Intervention and Simulation Network conducted by Meza and colleagues 8 showed that the 2021 USPSTF criteria would lead to greater increases in eligibility for Black, Hispanic, American Indian, and Alaska Native populations relative to White and Asian populations. 8 Comparing the 2021 and 2013 USPSTF criteria in their sample of BRFSS survey respondents, Liu et al 5 found that the proportion of those who met all criteria increased from 20.9% to 31.1%.…”
Section: Openmentioning
confidence: 99%
See 3 more Smart Citations